2021
DOI: 10.1055/a-1386-7434
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the polyp-based resect and discard strategy: a retrospective study

Abstract: Background: Standard colonoscopy practice requires removal and histological characterization of almost all small (<10 mm) and diminutive (≤5 mm) colorectal polyps found. The aim of this study was to test a simplified polyp-based resect and discard (PBRD) strategy that assigns surveillance intervals based only on size and number of small and diminutive polyps, without the need for pathology. Methods: A post hoc analysis was performed on patients enrolled in a prospective colonoscopy study. The primary outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
0
5
1
Order By: Relevance
“…In the second, post-procedural stage, it is decided whether retrieved polyps with dimensions between 3 mm and 5 mm are sent for a histopathological examination or are discarded, depending on the other two variables: the total number of polyps and the presence of polyps larger than 1 cm. Post hoc analysis showed that the accuracy of this algorithm was 98.6%, which far exceeded the advanced optical diagnosis accuracy of 71.6% that we reported, and is even higher than the AI-assisted NBI-trained expert accuracy of 90.2% previously reported in another study as well as the proposed 90% agreement with pathology-based management according to the 2020 US Multi-Society Task Force guidelines [23,24].…”
Section: Discussioncontrasting
confidence: 72%
“…In the second, post-procedural stage, it is decided whether retrieved polyps with dimensions between 3 mm and 5 mm are sent for a histopathological examination or are discarded, depending on the other two variables: the total number of polyps and the presence of polyps larger than 1 cm. Post hoc analysis showed that the accuracy of this algorithm was 98.6%, which far exceeded the advanced optical diagnosis accuracy of 71.6% that we reported, and is even higher than the AI-assisted NBI-trained expert accuracy of 90.2% previously reported in another study as well as the proposed 90% agreement with pathology-based management according to the 2020 US Multi-Society Task Force guidelines [23,24].…”
Section: Discussioncontrasting
confidence: 72%
“…Conversely, if diminutive (<5 mm) polyps are identified during colonoscopy, many of them have benign pathology and pose little to no malignant potential. Because of this, many clinicians have proposed a pluck-and-discard strategy to avoid wasting medical resources for pathologic analysis [ 50 , 51 ]. However, this method has not yet become common practice due to the fear of missing small malignant polyps.…”
Section: Discussionmentioning
confidence: 99%
“…The 5-year survival rate of early stage CRC exceeds 90% with a well-established screening program [4]. The American Society for Gastrointestinal Endoscopy has proposed "resect and discard" and "diagnose and leave" strategies, suggesting that non-neoplastic polyps can be left unresected [5][6][7]. This strategy is based on real-time polyp classification, which is cost-effective and saves time for endoscopists.…”
Section: Introductionmentioning
confidence: 99%